Effect of dietary sugars on dual-species biofilms of Streptococcus mutans and Streptococcus sobrinus – a pilot study - Oliveira, Rosa Virginia Dutra De; Albuquerque, Yasmin Etienne; Spolidorio, Denise Madalena Palomari; Koga-ito, Cristiane Yumi; Giro, Elisa Maria Aparecida; Brighenti, Fernanda Lourenção (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction Frequent consumption of sugars and the presence of Streptococcus mutans and Streptococcus sobrinus are correlated with higher caries experience.Objective The aim of this pilot study was to elucidate the effect of different fermentable carbohydrates on biomass formation and acidogenicity of S. mutans and S. sobrinus biofilms.Material and method Single and dual-species biofilms of S. mutans ATCC 25175 and S. sobrinus ATCC 27607 were grown at the bottom of microtiter plates at equal concentrations for 24 h at 37 °C under micro-aerobic atmosphere. Carbohydrates were added at 2% concentration: maltose, sucrose, glucose and lactose. BHI Broth (0.2% glucose) was used as negative control. Acidogenicity was assessed by measuring the pH of spent culture medium after 24 h, immediately after refreshing the culture medium and for the next 1 h and 2 h. Crystal violet staining was used as an indicator of the total attached biofilm biomass after 24 h incubation. Data were analyzed by two-way ANOVA followed by Bonferroni post hoc test. Significance level was set at 5%.Result All carbohydrates resulted in higher biomass formation in single- and dual-species biofilms when compared to the control group. Sucrose, lactose and maltose showed higher acidogenicity than the control group in both single- and dual-species biofilms after 24 h.Conclusion These findings indicate that the type of biofilm (single- or dual-species) and the carbohydrate used may influence the amount of biomass formed and rate of pH reduction.

ResumoIntrodução O consumo frequente de açucares e a presença de Streptococcus mutans e Streptococcus sobrinus estão correlacionados com maior experiência de cárie.Objetivo Elucidar o efeito de diferentes carboidratos fermentáveis na biomassa e acidogenicidade de biofilmes formados por S. mutans e S. sobrinus.Material e método Biofilmes única e dupla- espécie de S. mutans ATCC 25175 e S. sobrinus ATCC 27607 em concentrações iguais cresceram no fundo de placas de microtitulação por 24 h a 37 °C em microaerofilia. Maltose, sacarose, glicose e lactose foram adicionados a 2%. BHI caldo (0.2% glicose) foi usado como controle negativo. Acidogenicidade foi avaliada por meio da medição do pH do meio de cultura após 24 h, imediatamente após troca de meio e nas próximas 1 h e 2 h. Coloração por cristal violeta foi usada como indicador do total de biomassa aderida, após 24 h de incubação. Os dados foram analisados por teste ANOVA two way e Teste de Bonferroni. O nível de significância foi de 5%.Resultado Todos os carboidratos resultaram em maior formação de biomassa em ambos os tipos de biofilme (única ou dupla- espécie), quando comparado ao grupo controle. Sacarose, lactose e maltose mostraram maior acidogenicidade que o grupo controle após 24 h nos biofilmes única ou dupla-espécie, apenas após 24 h.Conclusão Os achados indicam que o tipo de biofilme (única ou dupla- espécie) e o tipo de carboidrato usado podem influenciar tanto na quantidade de biomassa formada quanto na taxa de redução do pH.
Efeito dos açucares da dieta em biofilme dupla espécie de Streptococcus mutans e Streptococcus sobrinus – um estudo piloto
Keywords: Biofilm; biomass; Streptococcus mutans; Streptococcus sobrinus; Biofilme; biomassa; Streptococcus mutans; Streptococcus sobrinus